Lactic acid does not cause muscle soreness - Kashubara, K. (Track Coach, 2018)
The advent of information technology has caused a revolution in education. Tonight, today's students can read studies published this morning. Never before has the newest information been so available. High school students in AP classes, and collegiate student-athletes, know more than ever before. Coaches need the athletes' trust and respect in order for coaches to help athletes reach their full potential. Students are going to class and learning that lactic acid is not the cause of muscular soreness. Lactic acid is not even the cause of the "burn." Students read the proof and study the facts for their tests. Then when they go to practice, and hear a coach talk about recovery runs "to flush lactic acid," the students may lose some respect for that coach. They may question the coach, thinking, "well if they think this, and it's wrong, what else are they wrong about?" We coaches mostly refer to what we were taught. We were taught the best information available at the time. Even now, when completing an internet search, hundreds of articles on workouts, soreness and recovery provide faulty lactic acid information. The purpose of this article is to help coaches relay recent scientific information to today's athletes in a way that they understand.